Remark on the Second Bounded Cohomology of Amalgamated Product of Groups - Faĭziev, Valeriy A.; Sahoo, Prasanna K. (Sarajevo Journal of Mathematics, 2024)
For any cardinal number M we construct examples of amalgamated products and HNN extensions of groups such that the dimension of the space of second bounded cohomologies is at least M. Also we describe the space of pseudocharacters of the group GL(2,F_2[z]). 2000 Mathematics Subject Classification. Primary: 20M15, 20M30, 39B82